2022
DOI: 10.2196/31839
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Web-Based Physical Activity Interventions on Depression and Anxiety Among College Students: Randomized Experimental Trial

Abstract: Background Depression and anxiety are growing issues for college students, with both aerobic resistance training and mindfulness yoga exercises known to be effective in reducing symptoms and severity. However, no known research is available comparing these 2 depression and anxiety interventions simultaneously and in a web-based environment. Objective This study aims to determine the effects of a web-based aerobic resistance exercise intervention (WeActi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
11
1
1
Order By: Relevance
“…By analogy, the findings of our study were also in line with those of a recent cross-sectional study stipulating that engaging in a moderate and high volume of exercise was associated with lower depression symptomatology in non-clinical adult individuals [ 133 ]. Nonetheless, even though our study did not support the findings related to the positive effects of PA on anxiety symptomatology reported by other scholars [ 132 , 133 , 134 ], it was consistent with some cross-sectional studies and randomised, controlled trials [ 135 , 136 , 137 ] and was able to indicate the absence of beneficial effects of PA on reducing anxiety symptoms.…”
Section: Discussioncontrasting
confidence: 50%
“…By analogy, the findings of our study were also in line with those of a recent cross-sectional study stipulating that engaging in a moderate and high volume of exercise was associated with lower depression symptomatology in non-clinical adult individuals [ 133 ]. Nonetheless, even though our study did not support the findings related to the positive effects of PA on anxiety symptomatology reported by other scholars [ 132 , 133 , 134 ], it was consistent with some cross-sectional studies and randomised, controlled trials [ 135 , 136 , 137 ] and was able to indicate the absence of beneficial effects of PA on reducing anxiety symptoms.…”
Section: Discussioncontrasting
confidence: 50%
“…No significant changes were noted between the groups. The results of the study showed the effectiveness of both intervention programs for improving students’ mental health [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, four were supplemented by an additional follow-up examination [ 27 , 29 , 30 , 35 ]. An analysis of the statistical methods used revealed that three authors used univariate pre-post methods (Wilcoxon test, t-test, Mann-Whitney U test) [ 34 , 35 , 38 ], six authors used linear models [ 27 , 29 , 32 , 33 , 36 , 37 ], three studies employed analysis of variance [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, a solution could be a web-based exercise program at home [ 9 , 10 ]. With the development of communication technology, people can participate in group exercises at home with guidance from an instructor through videoconferencing platforms such as the Zoom application (Zoom Video Communications) [ 11 , 12 ]. Although a web-based exercise through videoconferencing platform is beneficial, the feasibility, safety, and enjoyment of the web-based exercise program and ease of use of a web-based exercise delivery system should be carefully considered especially in older adults [ 13 ].…”
Section: Introductionmentioning
confidence: 99%